Municipal Solid Waste Management on Koh Nok by People’s Participation of Tha Kham Sub-district Municipality, Bang Pakong District, Chachoengsao Province - Mahadlek , Jongporn; kingmala, Piyawadee (Recent Science and Technology, 2020)
The objectives of this research were to 1) survey the general conditions of Koh Nok and its surrounding communities and collect the opinions of communities in the surrounding areas of Koh Nok about the solid waste problems and the waste management, 2) educate the community on waste management and create a community network that had the potential to preserve the environment around Koh Nok and surrounding communities, and 3) promote and coordinate among the community, community networks and government agencies to participate in activities at the area level. The samples were 30 volunteers in Moo 1. The tools used in this research were a questionnaire for public participation in the waste management, an attitude test on waste management, an assessment form for the participants. The data were analyzed and expressed as percentage, frequency, means, and standard deviations. The results showed that 1) the area of Koh Nok was a natural island caused by sediment deposition, living organisms that had developed into a relatively complete mangrove forest ecosystem. Most plants were mangrove trees, avicennia trees and nipa palm trees. The south of the island was eroded. The area has accumulated a lot of waste blown with water. The neighboring community of Koh Nok was Moo 1. Most houses were spread out but some areas were densely populated. The problem of solid was minimal. The opinions of communities around Koh Nok on solid waste problem can be concluded that the main factors that caused waste were garbage blown with the current and then accumulated. The result of attitude measurement was at a good level. The evaluation of the participation was at a medium level. 2) The overview of opinions participants was at a high level. The community network was created with 30 members to collect garbage on Koh Nok and in the communities. 3) The results of promotion, collaboration between community networks, communities and government revealed that the municipality helped cooperate and support community network activities and invited the community to participate in waste activities.